Prototype Smart Home Menggunakan Modul Wifi ESP8266 Dengan Aplikasi Telegram - Oktari, Nisa Gracella Aslamia; Nurdin, Ali; Rakhman, Abdul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Smart Home is a technology that can make it easier for users to manage comfort and safety at home so they can control the equipment used, homeowners can open the gate automatically and check the temperature and humidity of the existing room at home. Sometimes homeowners forget to turn off or turn on the equipment used, and forget to close the gate again when no one is at home. From the above problems made a tool that can be used as a remote home appliance controller or can also be called smart home. This tool uses the ESP8266 wifi module as the main device and sensor control that is connected to the Telegram Application to give commands to the ESP8266 wifi module so that it can control the equipment used and is at home.